Uncaria-derived alkaloids: A review on the mechanism in inducing apoptosis in oral squamous cell carcinoma - Ridho, Fiki Muhammad; Ulfah, Kamailiya; Aruan, Iren Angelia; Pramaztri, Naurah Nabilah; Laksono, Eko Puji; Putri, Aurellia Nuraini Anindito (International Journal of Pharmacology and Toxicology, 2024)
Alkaloids, the major secondary metabolite compounds identified in the genus Uncaria, exhibit the ability to induce apoptosis in oral squa-mous cell carcinoma (OSCC). Various potential alkaloids in herbal medicine have been explored and provided promising results, one of which is the potential to induce apoptosis. This study aims to provide a more comprehensive review of the mechanism of alkaloids derived from Uncaria in inducing apoptosis in OSCC. In the systematic search conducted, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were adhered to conduct this review through the databases, including PubMed, ScienceDirect, Wiley and a manual search using Google Scholar. According to the findings, this review states that several types of alkaloids derived from Uncaria that have been reviewed, such as hirsutine, rhynchophylline, isorhynchophylline, and hirsuteine, have different mechanisms in in-ducing apoptosis in OSCC, both through intrinsic and extrinsic pathways. The evidence presented in the present study provides an oppor-tunity for future research to determine the appropriate therapeutic dose based on the specific alkaloid, duration of therapeutic administration, and in vivo and/or in human testing.